Alarmins and Related Molecules in Elective Surgery - Strohalmová, Sabina; Levová, Kateřina; Kuběna, Aleš; Hoskovec, David; Krška, Zdeněk; Zima, Tomáš; Kalousová, Marta (Folia biologica, 2023)
Surgery is associated with alterations of alarmins' and related molecules' levels. The aim of this study was to investigate which biomarkers are most involved in surgery. The studied group consisted of 58 patients with inguinal or umbilical hernia or cholecystolithiasis and 21 healthy controls for compa-rison. We also added seven acute patients with appendicitis, cholecystitis and incarcerated hernia. Serum concentrations of soluble receptor of advanced glycation end-products (sRAGE), extracellular newly identified receptor for advanced glycation end-products binding protein (EN-RAGE), calprotectin, high mobility group box 1 (HMGB1) and interleukin 6 (IL-6) were analysed by ELISA before and after surgery. Preoperative concentrations of calprotectin were significantly decreased while concentrations of sRAGE were significantly increased in patients compared to controls; the concentrations of EN-RAGE and HMGB1 did not differ significantly. IL-6 levels were undetectable in elective patients preoperatively and in controls. Postoperatively, there was a significant increase of EN-RAGE, calprotectin, HMGB1, and IL-6 and a significant decrease of sRAGE compared to preoperative levels. In acute patients, all tested molecules except for sRAGE were significantly increased preoperatively, and sRAGE was significantly decreased. In contrast, after surgery, we could observe a further increase in IL-6; the other biomarkers did not differ significantly. We can conclude that the concentrations of all tested biomarkers are significantly influenced by elective surgery. The postoperative levels of all tested molecules increase except for sRAGE, whose level is significantly decreased after surgery. In acute states, these molecules are already increased, and the influence of surgery is, apart from IL-6, insignificant.
Keywords: Alarmins; Humans; produkty pokročilé glykace; Receptor for Advanced Glycation End Products; HMGB1 Protein; lidé; receptor pro konečné produkty pokročilé glykace; Leukocyte L1 Antigen Complex; Glycation End Products, Advanced; biologické markery; alarminy; Biomarkers; Interleukin-6; interleukin-6; protein HMGB1; leukocytární L1-antigenní komplex